Religious Authority within the Colonial Structure:The Kiai Penghulu of Banyumas and Local Social Dynamics (1922–1938) - Jamaluddin Jamaluddin; Syaiful Anam; Affaf Mujahidah (Regalia Institute, 2026)
The early twentieth century marked a crucial period in the transformation of the roles of kiai penghulu in Banyumas, particularly within the socio-religious and socio-cultural domains. Their integration into the colonial bureaucratic structure positioned kiai penghulu in a strategic role that enabled them to perform dual functions: as religious officials and as social actors mediating between colonial administrative interests and the religious needs of Muslim communities. In this context, kiai penghulu were not merely executors of normative religious duties but were also actively engaged in local processes of social change. This article examines the roles of kiai penghulu in Banyumas amid the evolving social dynamics shaped by the implementation of the Ethical Policy and the intensification of modernization in the Netherlands Indies. The study employs the historical method, encompassing heuristics, source criticism, interpretation, and historiography. The findings demonstrate that kiai penghulu in Banyumas played an active role in early twentieth-century social life through their involvement in religious organizations such as Muhammadiyah during the 1920s, participation in the establishment of grassroots financial institutions that later developed into Bank Rakyat Indonesia, and contributions to the dissemination of knowledge through writings published in Majalah Damai. This article contributes to the study of colonial Islamic socio-cultural history by highlighting local perspectives that position kiai penghulu as active agents of social change and by offering a fresh understanding of religious officials as mediators between the colonial state and Muslim society.